Association between oral health-related behaviors and quality of life of adolescents among three provinces in Northwest China - Hu, Xiao; Wang, Can; Gao, Jianghong; Tian, Jiangang; Li, Lingling; Li, Zhige; Guo, Kaixin; Huang, Ruizhe (Frontiers in Public Health, 2024)
ObjectiveTo assess the oral health-related quality of life (OHRQoL) of adolescents in Northwest China, and to explore the relationship between sociodemographic characteristics, oral health-related behaviors and OHRQoL.MethodsA cross-sectional survey of adolescents aged 12–15 years in Shaanxi, Gansu province and Ningxia Hui Autonomous Region of Northwest China was conducted by stratified cluster random sampling. Oral examinations were performed with World Health Organization (WHO) standards, and the condition of crowns and periodontal was recorded. Adolescents' oral health-related behaviors and OHRQoL were collected by questionnaire. Chi-square test and binary logistic regression analysis were used to examine the relationship.ResultsA total of 7,648 subjects were included. The prevalence of low OHRQoL which defined as a score higher than 0, was 83.8%. A low OHRQoL was most prevalent in Gansu Province and least prevalent in Shaanxi Province. Younger (OR = 0.73, CI = 0.60–0.87), female (OR = 1.27, CI = 1.11–1.44), rural (OR = 1.44, CI = 1.21–1.72), and mother with less education (OR = 0.69, CI = 0.60–0.81) all showed statistically significant influence on teenagers' OHRQoL. From a behavior perspective, teens' OHRQoL was correlated with their frequency of sugar consumption (OR = 1.72, CI = 1.41–2.10), dental appointment rate (OR = 1.29, CI = 1.064–1.57), self-assessment of oral health (OR = 3.09, CI = 2.29–4.19), DMFT index (OR = 1.19, CI = 1.04–1.37), number of teeth calculus (OR = 1.20, CI = 1.01–1.43), and dental trauma (OR = 0.47, CI = 0.39–0.57) over the previous year; however, brushing their teeth was not statistically significant.ConclusionsGenerally speaking, oral health-related behaviors—such as eating more sugary foods and scheduling dental appointments within the last year—have a significant negative impact on the quality of life of adolescents in Northwest China. Female, and adolescents from families with low educational backgrounds are more likely to be affected by such behaviors in their daily lives.